STUDENTS’ LANGUAGE LEARNING STYLES: AN ETHNOGRAPHIC CASE STUDY AT UIN WALISONGO SEMARANG - Muhammad Nafi Annury (Vision: Journal for Language and Foreign Language Learning, 2016)
This research is aimed at knowing kinds of  learning preferences the students intend most and types of learners’characteristics appear in ELT classrooms.This research was conducted through qualitative approach. The data are collected questionnaires, documentation, and observation. The result of this study shows that students of ELT program at UIN Walisongo Semarang tend to study by various kinds of  learning. Among students of  2A, 11.2% are visual students, 16.02% are audio-lingual, 5% are kinesthetic and the rest 14.11% are others, would use multimedia which available in the classroom. Whereas, students of 2B show that 13% of them are visual learners, 11%  are audiolingual learners, 6.72% are kinesthetics and the rest 13,72% are others. Students of 2C, 12% of them are visual learners, 11.17% are audiolingual, 7.25% are kinesthetics and the rest 14% are others.